Association Between Prediabetes and Erectile Dysfunction: A Meta-Analysis - Jin, Mingyu; Yuan, Shaoying; Wang, Bo; Yi, Luqi; Wang, Chenxia (Frontiers in Endocrinology, 2022)
Background: Diabetes has been associated with the increased risk of erectile dysfunction (ED). However, previous studies evaluating the association between prediabetes and ED showed inconsistent results. We performed a meta-analysis of observational studies to systematically evaluate the above association. Methods: Relevant observational studies were retrieved by search of PubMed, Embase, and Web of Science databases. A random-effect model which incorporated the potential intra-study heterogeneity was used for the meta-analysis. Subgroup analyses were performed to evaluate the influences of study characteristics on the outcome. Results: Nine studies (five matched case-control studies and four cross-sectional studies) were included. Age were adjusted or matched in all of the studies. Pooled results showed that compared to men with normoglycemia, men with prediabetes were associated with higher prevalence of ED (odds ratio = 1.62, 95% confidence interval: 1.28 to 2.07, P < 0.001; I2 = 78%). Subgroup analyses showed that the association was not significantly affected by definition of prediabetes, diagnostic tool for ED, or controlling of additional variables besides age (both P for subgroup difference > 0.05). However, the association between prediabetes and ED seemed to be stronger in case-control studies than that in cross-sectional studies, and in studies with younger men (mean age < 50 years) than in those with older men (mean age ≥ 50 years; both P for subgroup difference < 0.05). Conclusions: Prediabetes is associated with higher prevalence of ED, which may be independent of age of the males and may be stronger in young men.